1999
DOI: 10.1152/ajpcell.1999.277.5.c955
|View full text |Cite
|
Sign up to set email alerts
|

RhoA inactivation enhances endothelial barrier function

Abstract: The modulation of endothelial barrier function is thought to be a function of contractile tension mediated by the cell cytoskeleton, which consists of actomyosin stress fibers (SF) linked to focal adhesions (FA). We tested this hypothesis by dissociating SF/FA with Clostridium botulinum exoenzyme C3 transferase (C3), an inhibitor of the small GTP-binding protein RhoA. Bovine pulmonary artery endothelial cell (EC) monolayers given C3, C3 + thrombin, thrombin, or no treatment were examined using a size-selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
86
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 25 publications
4
86
1
2
Order By: Relevance
“…Such approaches have been previously used to demonstrate diabetes-related increase in permeability of coronary microvasclature to albumin (21)(22)(23) The precise mechanisms responsible for these observations are not clear. One potential explanation is that statins alter rho-GTPase activity (11,24 -28), and rho signaling pathways have been shown to have a critical role in endothelial barrier function (9,10). However, this biochemical pathway is dependent on the inhibition of HMGCoA reductase activity (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such approaches have been previously used to demonstrate diabetes-related increase in permeability of coronary microvasclature to albumin (21)(22)(23) The precise mechanisms responsible for these observations are not clear. One potential explanation is that statins alter rho-GTPase activity (11,24 -28), and rho signaling pathways have been shown to have a critical role in endothelial barrier function (9,10). However, this biochemical pathway is dependent on the inhibition of HMGCoA reductase activity (11).…”
Section: Discussionmentioning
confidence: 99%
“…Another likely contributor to these changes is the activation of protein kinase C that is shown to play an important role in increased permeability of the peripheral and cerebral circulation (7,8). Finally, recent studies have shown that inactivation of the rho-GTPase has a critical role in endothelial barrier function (9,10).…”
mentioning
confidence: 99%
“…ASF formation under stimulated and / or stress conditions and the connection of the tip of ASF to focal adhesion units (FAU) and other cell adhesion factors have been documented (29,30). In the internal surface of the plasma membrane, FAU connect cytoskeleton and ASF.…”
Section: +mentioning
confidence: 99%
“…Another class of critical regulatory proteins in regulation of endothelial barrier function is the family of Rho GTPases (2,9,14,36,45,47). The family consists of 20 distinct members [Rho (A, B, C); Rac (1, 2, 3); Cdc42; TC10; TCL; Chp (1, 2); RhoG; Rnd (1, 2, 3); RhoBTB (1, 2); RhoD; Rif; and TTF)] (15), of which Cdc42, Rac1, and RhoA are the most characterized (6) and are essential in the relay of signals to the actin cytoskeleton in regulation of activities such as cell adhesion, motility, cell cycle progression, and apoptosis.…”
mentioning
confidence: 99%